NDSH 1012 (Prabhat) : A high yielding and high oil content sunflower hybrid suitable for Andhra Pradesh: NDSH 1012 : A HIGH YIELDING AND HIGH OIL CONTENT SUNFLOWER HYBRID FOR ANDHRA PRADESH - S NEELIMA; K ASHOK KUMAR; K VENKATARAMANAMMA; V JAYALAXMI (Journal of Oilseeds Research, 2018)
Sunflower is one of the most important edible oilseed crops in the world including India due to its wide range of adaptability and high oil content. The feasibility studies conducted at the time of introduction of sunflower cultivation in India indicated that Andhra Pradesh is ideally suited for growing sunflower. Though, a large number of private sector hybrids are available in the market, quality seed is always a question. Of late, AICRP on sunflower scheme at Regional Agricultural Research Station, ANGRAU, Nandyal, Andhra Pradesh has developed a sunflower hybrid 'PRABHAT' (NDSH 1012), which is a short duration and a high oil yielding and suitable for cultivation in Andhra Pradesh. It is a robust plant type, matures in 90-95 days with a yield potential of 20-25 q/ha (irrigated condition) and an oil content of 40-41%. In All India coordinated trials during kharif 2014 and rabi 2015-16, 'NDSH 1012' registered an increase of oil yield by 12.2 % and 5.3 % over national checks KBSH 44 and DRSH 1, respectively. Moreover, 'NDSH 1012' was found to be moderately resistant to downy mildew disease. Hence, it can be concluded that cultivation of 'NDSH 1012' can be a better option for improving the productivity ofsunflower in Andhra Pradesh.